Abstract Distributed Engine (ADE): A Library for Data Consistency in Distributed Virtual Environments - Pires, F.; Dias, J. (Atas do 15º EPCG - Encontro Português de Computação Gráfica, 2007)
The subject of this paper is Distributed Virtual Environments. It describes the hardware and software architecture for an immersive distributed Virtual Reality system being built in the south of Portugal, the CAVEHOLLOWSPACE of Lousal. The proposed architecture is based on master/slave architecture and includes various modules and tools for the R&D community. On top of it, the CAVE-HOLLOWSPACE of Lousal features, specifically, Newton physics and spatial sound client/server modules. Additionally to the architecture design, we present an object-oriented library for 3D virtual world distribution, used by the two mentioned modules, and for distributing the simulation state (Abstract Distributed Engine - ADE). The paper also focuses on third-party libraries chosen, on how they cooperate and how they impact the overall system.